Language Proficiency Entails Tuning Cortical Activity to Second Language Speech. (1st April 2021) - Lizarazu, Mikel; Carreiras, Manuel; Bourguignon, Mathieu; Zarraga, Asier; Molinaro, Nicola
Abstract: Cortical tracking of linguistic structures in speech, such as phrases (<3 Hz, delta band) and syllables (3–8 Hz, theta band), is known to be crucial for speech comprehension. However, it has not been established whether this effect is related to language proficiency. Here, we investigate how auditory cortical activity in second language (L2) learners tracked L2 speech. Using magnetoencephalography, we recorded brain activity from participants listening to Spanish and Basque. Participants were Spanish native (L1) language speakers studying Basque (L2) at the same language center at three different levels: beginner (Grade 1), intermediate (Grade 2), and advanced (Grade 3). We found that 1) both delta and theta tracking to L2 speech in the auditory cortex were related to L2 learning proficiency and that 2) top-down modulations of activity in the left auditory regions during L2 speech listening—by the left inferior frontal and motor regions in delta band and by the left middle temporal regions in theta band—were also related to L2 proficiency. Altogether, these results indicate that the ability to learn an L2 is related to successful cortical tracking of L2 speech and its modulation by neuronal oscillations in higher-order cortical regions.